Estratégias técnicas-interpretativas utilizadas em diferentes versões da obra Circos sobre uma Viagem Imaginária – Paisagem III “A Cidade”, para percussão e eletrônicos. - Freire, Pedro Henrique Machado (2017)
We present a reflection on the process of study and performance of the work Circos sobre uma Viagem Imaginária – Paisagem III “A Cidade” of the composer Danilo Aguiar. Originally, this work was composed for a percussion setup and electronics in real time, where through a motion sensor, the physical gestures of the performer generate and control electronic sounds. A second version of this work was created by eliminating real-time interaction. We reflect here on technical and interpretative strategies adopted in the different versions.